Implementasi Program “Sinergi Meraih Prestasi” di SMP Negeri 1 Krangkeng Kabupaten Indramayu - Asep Darmawan (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This study aims to describe the implementation of the Synergy to Achieve Achievement program at SMP Negeri 1 Krangkeng Kabuapaten Indramayu. The Synergy Program is one of the efforts to overcome various problems of low achievement in schools. This study used qualitative descriptive method. The results showed that the Synergy Program has provided good benefits in improving school achievement, including: (1) increasing students' abilities/competencies in reading and translating the Quran, (2) increasing student achievement in the fields of science and technology in various olympics, (3) increasing student achievement in the arts and scouts, and (4) increasing student achievement in literature and literacy. The increase in student achievement is in line with the increase in teacher achievement in various fields. The implementation of the Synergy to Achieve Achievement program in school management can improve school achievement.